2014
DOI: 10.1152/jn.00071.2014
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine functionally reorganizes neocortical microcircuits

Abstract: Runfeldt MJ, Sadovsky AJ, MacLean JN. Acetylcholine functionally reorganizes neocortical microcircuits. J Neurophysiol 112: 1205-1216, 2014. First published May 28, 2014 doi:10.1152/jn.00071.2014.-Sensory information is processed and transmitted through the synaptic structure of local cortical circuits, but it is unclear how modulation of this architecture influences the cortical representation of sensory stimuli. Acetylcholine (ACh) promotes attention and arousal and is thought to increase the signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Here, by studying isolated microcircuits within brain slices, we demonstrate unequivocally that the decorrelations observed in vivo can emerge as a result of cholinergic modulation acting directly on microcircuits. (Interestingly, whereas we studied ongoing patterns of spontaneous network activity similar to those believed to mediate attentional effects in vivo , another recent in vitro study (4) showed that acetylcholine decorrelates the latency to the first spike in somatosensory neurons responding to thalamic input).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, by studying isolated microcircuits within brain slices, we demonstrate unequivocally that the decorrelations observed in vivo can emerge as a result of cholinergic modulation acting directly on microcircuits. (Interestingly, whereas we studied ongoing patterns of spontaneous network activity similar to those believed to mediate attentional effects in vivo , another recent in vitro study (4) showed that acetylcholine decorrelates the latency to the first spike in somatosensory neurons responding to thalamic input).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, a major barrier to identifying such circuit-level abnormalities has been recording from large numbers of neurons simultaneously. However, advances in imaging and electrophysiological techniques have made it possible to characterize patterns of circuit-level activity by, for example, calculating correlations between neurons (3, 4). Despite these advances, cognitive processes are associated with complex neural dynamics embedded within a high dimensional state space.…”
Section: Introductionmentioning
confidence: 99%
“…Using diverse research approaches ranging from assessing effects of selective lesions, amperometric measures of the fast, phasic, or transient component of cholinergic neurotransmission, microdialysis measures of levels of cholinergic neuromodulation, neurophysiological recordings, and optogenetic generation and attenuation of fast cholinergic transients in performing rodents, the basal forebrain cholinergic projection system to the cortex has been shown to mediate, necessarily, the incorporation of cues into cortical circuitry, thereby allowing such cues to control behavior (Avery, Dutt, & Krichmar, 2014; Goard & Dan, 2009; Gritton et al, 2016; Howe et al, 2013; Howe et al, 2017; McGaughy et al, 1996; Parikh, Kozak, Martinez, & Sarter, 2007; Pinto et al, 2013; Runfeldt, Sadovsky, & MacLean, 2014; Sarter, Howe, & Gritton, 2015; Sarter, Lustig, Berry, et al, 2016; Sarter, Lustig, Howe, Gritton, & Berry, 2014). Furthermore, levels of cholinergic neuromodulation influence the likelihood and the amplitudes of cholinergic transients that cause the detection of cues in attentional contexts (for a circuitry model underlying this interaction see Hasselmo & Sarter, 2011).…”
Section: Sts and Gts As Models For Research On Opponent Cognitive-motmentioning
confidence: 99%
“…These spontaneous activations are blocked by inhibitors of excitatory neurotransmitters (Cossart et al 2005;Runfeldt et al 2014) and are not recapitulated by a rate-matched null model of independent Poisson neurons (Chambers and MacLean 2015).…”
mentioning
confidence: 95%